2019
DOI: 10.3390/rs11141667
|View full text |Cite
|
Sign up to set email alerts
|

Fault Slip Model of the 2018 Mw 6.6 Hokkaido Eastern Iburi, Japan, Earthquake Estimated from Satellite Radar and GPS Measurements

Abstract: In this study, Sentinel-1 and Advanced Land Observation Satellite-2 (ALOS-2) interferometric synthetic aperture radar (InSAR) and global positioning system (GPS) data were used to jointly determine the source parameters and fault slip distribution of the Mw 6.6 Hokkaido eastern Iburi, Japan, earthquake that occurred on 5 September 2018. The coseismic deformation map obtained from the ascending and descending Sentinel-1 and ALOS-2 InSAR data and GPS data is consistent with a thrust faulting event. A comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…We found that the axis of σ 1 is oriented to ENE-WSW and the axis of σ 1 is close to be horizontal or tilting down to the eastward. The fault plane of the main shock dips approximately 70° eastward (Kobayashi T et al 2019;Guo et al 2019). The pl = 19° of σ 1 may promote the reverse faulting slip of the main shock.…”
Section: Orientation Of Principal Stressesmentioning
confidence: 99%
“…We found that the axis of σ 1 is oriented to ENE-WSW and the axis of σ 1 is close to be horizontal or tilting down to the eastward. The fault plane of the main shock dips approximately 70° eastward (Kobayashi T et al 2019;Guo et al 2019). The pl = 19° of σ 1 may promote the reverse faulting slip of the main shock.…”
Section: Orientation Of Principal Stressesmentioning
confidence: 99%
“…We found that the axis of σ 1 is oriented to ENE-WSW and the axis of σ 1 is close to be horizontal or tilting down to the eastward. The fault plane of the main shock dips approximately 70° eastward (Kobayashi et al 2019a,b;Guo et al 2019). The pl = 19° of σ 1 may promote the reverse faulting slip of the main shock.…”
Section: Orientation Of Principal Stressesmentioning
confidence: 99%
“…GPS observations can provide 3D surface deformation, but the GPS stations are relatively sparse and have low spatial resolution, which is insufficient to show detailed surface movement. Consequently, many researchers fused these two data sets to infer the 3D surface deformation because InSAR and GPS data can complement each other in spatial and temporal resolutions [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%